2011
DOI: 10.1016/j.jvs.2011.06.118
|View full text |Cite
|
Sign up to set email alerts
|

Early results and lessons learned from a multicenter, randomized, double-blind trial of bone marrow aspirate concentrate in critical limb ischemia

Abstract: In this multicenter, randomized, double-blind, placebo-controlled trial of autologous bone marrow cell therapy for CLI, the therapy was well tolerated without significant adverse events. The BMAC group demonstrated trends toward improvement in amputation, pain, quality of life, Rutherford classification, and ABI when compared with controls. This pilot allowed us to identify several areas for improvement for future trials and CLI studies. These recommendations include elimination of treadmill testing, stratific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 58 publications
(38 reference statements)
3
42
0
2
Order By: Relevance
“…As reported in many studies, intramuscular administration of BM-MNCs in ischemic limb improved clinical outcomes including improved ankle brachial index, pain-free walking distance/time, wound healing and limb salvage [73][74][75][76]. In support, recent studies confirmed the clinical improvement in patients with severe limb ischemia following intramuscular administration of BM-MNCs in terms of lower amputation rates and improved ankle-brachial index [77][78][79]. In contrast, a small randomized trial reported non-significant trends toward improved ankle brachial index, and wound healing in patients treated with BM-MNC [80].…”
Section: Therapeutic Utility Of Bm-mncs In CLIsupporting
confidence: 54%
“…As reported in many studies, intramuscular administration of BM-MNCs in ischemic limb improved clinical outcomes including improved ankle brachial index, pain-free walking distance/time, wound healing and limb salvage [73][74][75][76]. In support, recent studies confirmed the clinical improvement in patients with severe limb ischemia following intramuscular administration of BM-MNCs in terms of lower amputation rates and improved ankle-brachial index [77][78][79]. In contrast, a small randomized trial reported non-significant trends toward improved ankle brachial index, and wound healing in patients treated with BM-MNC [80].…”
Section: Therapeutic Utility Of Bm-mncs In CLIsupporting
confidence: 54%
“…He was enrolled in a pilot trial using bone marrow-derived stem cells, which were collected, processed, and immediately returned to the patient in the same procedure (2,7). In this procedure, a nonspecifi c mononuclear cell mix was implanted with minimal time spent outside the patient's body.…”
Section: Discussionmentioning
confidence: 99%
“…When it was determined that the patient had no additional revascularization options for limb salvage, he was enrolled in Harvest Technologies' "Feasibility Study of the Safety and Activity of Autologous Bone Marrow Aspirate Concentration (BMAC) for the Treatment of Critical Limb Ischemia Due to Peripheral Arterial Occlusive Disease" (2). His right ankle brachial index at the time of referral was 0.1, with a toe brachial index of 0.…”
Section: Case Presentationmentioning
confidence: 99%
“…since that time, numerous other studies have examined the efficacy and safety of cell therapy for Pad, with varying results (tables 1 and 2). [22][23][24][25][26][27][28][29][30][31][32][33] Most clinical trials of cell therapy for Pad have consisted of uncontrolled patient series, with few randomized, properly controlled studies. sample sizes have been relatively small, with most studies enrolling fewer than 50 patients.…”
Section: Vascular Regeneration In Padmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32][33] Procedures associated with cell therapy, such as bone marrow aspiration and injection, were generally well-tolerated by the patients, with few adverse events reported. hence, current data is promising, and safety concerns do not outweigh the promise of potential benefit, which must now be tested in definitive clinical trials.…”
Section: Vascular Regeneration In Padmentioning
confidence: 99%